Impression management tactics in the CEO statements of Turkish sustainability reports - Caliskan, Arzu Ozsozgun; Esen, Emel; Barkemeyer, Ralf (WILEY, 2021)
In this study, we construct a classificatory scheme of impression management tactics and apply it to a sample of sustainability report and annual report CEO statements issued by large Turkish companies. We find a wide range of impression management tactics applied in both types of CEO statements. However, impression management in sustainability report CEO statements emerges as more limited and uniform, revealing clearer prioritizations of impression management tactics when compared to annual report CEO statements. Sustainability report CEO statements emphasize tactics that allow the company to highlight carefully selected, isolated aspects of their sustainability engagement. At the same time, they rarely employ tactics that are geared towards more systematic (quantitative) performance evaluation. We attribute these differences to the way in which corporate sustainability performance is commonly conceptualized and evaluated, emphasising qualitative performance dimensions rather than the reporting of quantitative performance metrics. This results in the application of a different impression management tactics mix and limits the usefulness of sustainability reports as an accountability mechanism when compared to corporate annual reports. In addition, we provide tentative evidence for the context-specific nature of impression management, with the choice of impression management tactics reflecting the institutional environment a company is based in.
Keywords: CORPORATE SOCIAL-RESPONSIBILITY; CONSTRUAL-LEVEL THEORY; ORGANIZATIONAL POLITICS; SELF-PRESENTATION; PERFORMANCE; DISCLOSURE; LEGITIMACY; STRATEGIES; COMPANIES; DETERMINANTS; Business & Economics; Social Sciences - Other Topics